Presentation of a Mental Skills Model for General Science Students - Jasim Mohammed AlAbdullah, Sarah; Sharifi, Asghar; Mijwil Al-Isawi, Mushreq Mohammed; Saadatmand , Zohreh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aimed to identify and explain the dimensions and components of mental skills among general science students to provide a theoretical framework for enhancing these skills.Methodology: This study employed a qualitative approach based on grounded theory. Data were collected through in-depth semi-structured interviews with 18 students and relevant experts and analyzed using qualitative data analysis methods, including open, axial, and selective coding. ATLAS.ti software, version 8, was used for data analysis.Findings: Data analysis resulted in the extraction of 252 initial conceptual codes. These concepts were categorized into five main conceptual codes and 17 sub-conceptual codes, encompassing various dimensions of students' mental skills. The most significant identified dimensions include scientific thinking and analysis, creative and innovative thinking, management and organization, logical and systematic thinking, and research and scientific skills.Conclusion: Mental skills among general science students, as a key factor in academic and research success, consist of a set of abilities that are directly related to academic performance. Enhancing these skills can improve learning quality, the ability to solve complex scientific problems, and students' academic progress. The findings of this study suggest that educational institutions should focus on training critical thinking skills, creativity, time management, and scientific research to create a conducive environment for student development. Additionally, conducting further research to examine the impact of environmental and social factors on mental skills can contribute to a more comprehensive understanding of this field.